WHY DO INDONESIAN CHILDREN UNDER TWO YEARS OF AGE FAIL TO ACHIEVE MINIMUM DIETARY DIVERSITY? - Arina Nurul Ihsani; Diah Mulyawati Utari (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Minimum Dietary Diversity (MDD) is a key Infant and Young Child Feeding (IYCF) indicator that assesses the micronutrient adequacy of diets among children aged 6-23 months by measuring consumption from at least five out of eight defined food groups in the previous day. Inadequate MDD is associated with increased risk of nutritional problems in childhood. This study aimed to identify the determinants of inadequate MDD among children aged 6-23 months in Indonesia. This cross-sectional study used secondary data from the 2018 Indonesian Basic Health Research. The sample comprised 10,800 children aged 6-23 months, selected using total sampling based on inclusion and exclusion criteria. Bivariate analysis revealed significant associations between inadequate MDD and several factors (p < 0,05): child's age, mother's age, mother's education level, antenatal care (ANC) frequency, place of delivery, postnatal care (PNC) services, place of residence, and child growth monitoring. In multivariate logistic regression, child's age was the most dominant factor associated with inadequate MDD (adjusted odds ratio [aOR] = 2.762, 95% CI: 2.507–3.043, p < 0.0005). These findings provide evidence to inform nutrition policies and programs, particularly those targeting improved IYCF practices and complementary feeding in Indonesia.